(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The publication deals with linguistically and stylistic tools to identify the most notable characteristics of the specific idiostyle of writer and his outlook on the example of the astral world model Irina Zhylenko’ poetry, means of language explication, which are temporal counterparts – metalogical images of seasons.In the Ukrainian language world cyclical understanding of time prevails over the line (this is because people began to understand it more specifically and to bind its course with their employment, distinguishing between the abstract concept of “time” at a specific intervals (cycles) associated with the movement astronim’s in outer space and, consequently, changes in nature).Poetry Irene Zhylenko certifies functioning of autologous and metalogical images seasons. Metalogical temporal correspondences was constituted on folk images simultaneously observe copyright rethinking. Poetry of Irene Zhylenko certifies functioning of autologous and metalogical images seasons. Metalogical temporal correspondences were constituted on folk images simultaneously observed copyright rethinking.Spring refers to the state of mind. The vitality of the human author identifies with the concept “spring”, that achieving high goals, bright dreams, beautiful wishes and sincere feelings. Thesis there is determined such associative chains spring – light – silver gold – the morning of the fire – wind – Flowering branches – sun – the bride thunder light – people. Functional synestesy is the image of man-spring, when lyrical heroine identifies its state on the state of nature. Summer appears as a correlate of mental state – of joy. The image of fall is compared with a time when the soul dreams. Fluidity of this world, that really is truly a living soul – the soul bloom. The opinion by the author embodies the contrast in verses keywords life / death; neglect / flowering; earth / divinity; soul / earth / God. The prospect of further research is to study the functionality of linguistic units to describe correlates of earth model of the world.